Offshore Exploration For Hydrocarbons In Indonesia - Dr. B Situmorang (Scientific Contributions Oil and Gas, 1985)
Indonesian offshore areas in 1985 are still the loci of an active exploration program.  Exploration activities are anticipated to be at the same level as in 1984. A new ofl field in the East Java Sea (the Madura field) began production in September 1985 with initial production of 10.9 MBOPD.  The month of August 1985 is marked by the significant oil and gas discovery in the Banggai basin, offshore East Sulawesi, where the Tlaka-1 exploratory well flowed 3864 BOPD (29° API) and 1.1 MMSCF gas (60 ppm HS) from  Middle Miocene plat-form carbonates.  Together with exploration drillings in the area beyond the continental shelf which have been started since February 1984 such as in the area north of Lombok, the discovery will encrease enthusiasm for exploration of the frontier areas especially in the geologically complex reglon of Eastern Indonesia.  It also reveals that potential accumulation of hydrocarbons could also occur within the collision complex.